Religious Aggressiveness In Scales of Interfaith Communication - Rosyad, Rifki; Iskandar, Amin Rais; Mamin, Mamin (STAI AL-FALAH CICALENGKA, 2022)
Aggressive behavior (aggressiveness) often appears to trigger conflicts between religious communities. Conflicts occur that are triggered by aggressive attitudes in verbal and nonverbal forms. The response to uncontrolled verbal aggressiveness increases in the form of physical aggressiveness and/or nonverbal communication. This article aims to reveal and analyze how to control aggressive behavior in relationships between different religions between Muslims, Jews and Christians. Referring to the results of the review, it shows that one effective way to control aggressive behavior is through implementing inter-religious dialogue and giving punishment as a consequence of this aggressive attitude. The results of the analysis also show the importance of improving the image of religion from hostility, disputes and disputes that lead to conflict between people of different religions through a cross-cultural communication approach. Keywords: aggressiveness, religious conflict, interfaith communication Abstrak Perilaku agresif (agresivitas) seringkali muncul menjadi pemicu konflik antar umat beragama. Konflik terjadi muncul dipicu oleh sikap agresif dalam bentuk verbal maupun nonverbal. Respon atas agresivitas verbal tersebut yang tidak terkontrol meningkat pada bentuk agresivitas fisik, dan atau komunikasi nonverbal. Artikel ini bertujuan mengungkap dan menganalisis bagaimana mengendalikan perilaku agresif dalam relasi kehidupan berbeda agama antara Islam, Yahudi, dan Kristen. Mengacu pada hasil review menunjukkan bahwa salah satu cara efektif dalam mengendalikan perilaku agresif melalui pelaksanaan dialog antarumat beragama serta memberi hukuman (punishment) sebagai konsekuensi sikap agresif tersebut. Hasil analisis juga menunjukkan pentingnya memperbaiki citra agama dari permusuhan, perselisihan dan pertikaian yang menjurus pada konflik antarumat berbeda agama melalui pendekatan komunikasi lintas budaya. Kata Kunci: agresivitas, konflik agama, komunikasi lintas agama